The Effects of Government Protectionism: An Awareness, Motivation, Capability Approach - Bloodgood, James M.; Bloodgood, Jane A. (Journal of Applied Business and Economics, 2024)
Firms in developed countries frequently struggle with low-cost foreign competition. This is somewhat perplexing given the historical advantages firms have in developed countries. We examine how these firms respond to market entry by low-cost foreign competitors. Their responses and outcomes vary depending on the government’s degree of intervention. Using the global steel industry as an example, the awareness, motivation, capability (AMC) framework is used to structure firm decision-making. We find that applying the AMC suggests that firm responses depend on government trade interventions, thus recommending firms and their governments integrate their efforts to enhance beneficial outcomes for firms and society.